The impact of childbirth-related post-traumatic stress on a couple's relationship: a systematic review and meta-synthesis. (1st January 2018) - Delicate, A.; Ayers, S.; Easter, A.; McMullen, S.
Abstract: Objective : This review aimed to identify the impact of childbirth-related post-traumatic stress disorder (PTSD) or symptoms (PTSS) on a couple's relationship. Background: Childbirth can be psychologically traumatic and can lead to PTSD. There is emerging evidence that experiencing a traumatic birth can affect the quality of the couple's relationship. This is an important issue because poor-quality relationships can impact on the well-being of partners, their parenting and the welfare of the infant. Methods : A systematic search was conducted of Amed, CENTRAL, Cinahl, Embase, Maternity and Infant Care, Medline, MITCognet, POPLINE, PsycARTICLES, PsycBITE, PsycINFO, Pubmed and Science Direct. Additionally, grey literature, citation and reference searches were conducted. Papers were eligible for inclusion if they reported qualitative data about parents who had experienced childbirth and measures of PTSD or PTSS and the relationship were taken. Analysis was conducted using meta-ethnography. Results : Seven studies were included in the meta-synthesis. Results showed that childbirth-related PTSD or PTSS can have a perceived impact on the couple's relationship and five themes were identified: negative emotions; lack of understanding and support; loss of intimacy; strain on the relationship; and strengthened relationships. A model of proposed interaction between these themes is presented. Conclusions : The impact of childbirth-related PTSD or PTSS on the couple's relationships is complex. As the quality of the couple relationship is important to family well-being, it is important that healthcare professionals are aware of the impact of experiencing psychologically traumatic childbirth as impetus for prevention and support.